July protests shutdown (Cuba) - Voidly (2021)
CRITICAL severity censorship detected in Cuba. Confidence: 90%. Data sourced from OONI.
Censorship Incident ID: CU-2021-0001
Keywords: censorship; CU; censorship; critical